2016
DOI: 10.1007/s10237-016-0849-3
|View full text |Cite
|
Sign up to set email alerts
|

The effective elastic properties of human trabecular bone may be approximated using micro-finite element analyses of embedded volume elements

Abstract: word count: 249 Total word count: 3393Attachments: 5 figures and 2 tables + 1 figure and 4 tables in the appendices 2 Disclosure pageThe authors have no conflict of interest to report. AcknowledgmentsThe script manager Medtool (www.dr-pahr.at) was used to generate the µFE models, start the computations and analyse the results. The authors would like to thank Prof. Bert van Rietbergen for sharing the µCT data. Karol Daszkiewicz is supported by grants from the are also gratefully acknowledged. AbstractBoundary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 44 publications
1
27
0
Order By: Relevance
“…In this process, it is necessary to assign material properties to the bone tissue and that is not a trivial issue. Usually, no direct influence of the mineral content is taken into account and typical isotropic elastic constants are considered (Ulrich et al, 1998;Roque et al, 2013;Daszkiewicz et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In this process, it is necessary to assign material properties to the bone tissue and that is not a trivial issue. Usually, no direct influence of the mineral content is taken into account and typical isotropic elastic constants are considered (Ulrich et al, 1998;Roque et al, 2013;Daszkiewicz et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a study completely based on numerical simulations is the only alternative even though the results cannot be currently validated experimentally. The use of kinematic uniform boundary conditions in the μFE analyses could also be considered a limitation, as they are known for providing an upper bound of the stiffness tensor (Pahr and Zysset, 2008 ; Wang et al, 2009 ) or macroscopic yield (Panyasantisuk et al, 2015 ), and may also affect the damage morphology when compared to the in situ case (Daszkiewicz et al, 2017 ). We also assume that the orthotropic directions do not rotate during loading, which may be a valid assumption for the considered range of strains.…”
Section: Discussionmentioning
confidence: 99%
“…KUBCs showed a stiffer response especially at lower BV/TV values. Moreover, Daszkiewicz et al and Wili et al showed that apparent elastic and yield properties determined with PMUBCs are close to an embedded configuration of cubic RVEs of trabecular bone. Therefore, in the present study, PMUBCs are applied in the μFE analyses as well.…”
Section: Introductionmentioning
confidence: 93%